The orientation of future cinema : technology, aesthetics, spectacle - Isaacs, Bruce (Bloomsbury Academic, 2013)
What is the fate of cinema in an age of new technologies, new aesthetic styles, new modes of cultural production and consumption? What becomes of cinema and a century-long history of the moving image when the theatre is outmoded as a social and aesthetic space, as celluloid gives over to digital technology, as the art-house and multiplex are overtaken by a proliferation of home entertainment systems? The Orientation of Future Cinema offers an ambitious and compelling argument for the continued life of cinema as image, narrative and experience. Commencing with Lumière''s Arrival of a Train at.